Autism spectrum disorder and anorexia nervosa: an Italian prospective study - Jacopo Pruccoli; Altea Solari; Letizia Terenzi; Elisabetta Malaspina; Marida Angotti; Veronica Pignataro; Paola Gualandi; Leonardo Sacrato; Duccio Maria Cordelli; Emilio Franzoni; Antonia Parmeggiani (BMC, 2021)
Abstract Background Potential overlaps exist between psychopathological features of Anorexia Nervosa (AN) and Autism Spectrum Disorder (ASD). The impact of malnutrition on autistic traits in patients with AN should be considered. This study investigates possible associations among the psychopathology of Eating Disorders (EDs), ASD traits and BMI in a group of young patients with AN, using the EDI-3 (Eating Disorder Inventory-3) test and gold-standard measures for ASD. Methods Prospective study involving 23 inpatients admitted to an Italian Centre for paediatric ED. ASD traits and ED psychopathology were assessed administering the ADOS-2 (Autism Diagnostic Observation Schedule-2), AQ (Autism Quotient) and EDI-3 tests. Both present and past autistic traits were investigated using different versions of AQ. Correlations were adjusted for BMI, Obsessive Compulsive Disorder (OCD) comorbidity and concurrent antipsychotic treatments. Results An ASD diagnosis was possible in 22% of patients. Significant correlations were documented between ASD traits and ED psychopathology: AQ total-Interpersonal problems (IPC) (p = 0.041); AQ total-Global psychological maladjustment (GMPC) (p = 0.027); AQ social skills-Ineffectiveness (IC) (p = 0.018); AQ social skills-IPC (p = 0.019); AQ social skills-Affective problems (APC) (p = 0.025); AQ social skills-GMPC (p = 0.007); AQ attention switching-IPC (p = 0.020); ADOS-2 imagination-IC (p = 0.035). These correlations were independent of BMI, OCD and antipsychotic treatments. Conclusions ASD traits presented high prevalence in a group of young inpatients with AN. These traits were significantly correlated to 4 specific EDI-3 subscales and independent of BMI. This is the first study to investigate the relationship between ASD traits as measured with gold-standard measures, EDI-3 scores, and BMI.